1993
DOI: 10.1111/j.1365-3083.1993.tb03309.x
|View full text |Cite
|
Sign up to set email alerts
|

From the Structure of Antibodies to the Diversification of the Immune Response

Abstract: Cuando se acerca elfin, escribió Cartaphilus, ya no quedan imágenes de1 recuerdo; sólo quedan palabras. Palabras, palabras desplazadas y mutiladas, palabras de otros, fué la pobre limosna que le dejaron las horas y los siglos. J. L. BorgesWhen an animal is infected, either naturally or by experimental injection, with a bacterium, virus, or other foreign body, the animal recognises this as an invader and acts in such a way as to remove or destroy it. There are millions of different chemical structures that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 64 publications
0
4
0
1
Order By: Relevance
“…Here, we examined the sequences of the VL genes expressed by the same cells from which the VH genes were derived. We found that the VL genes had Murine antibodies were obtained after secondary immulnization with the hapten phenyloxazolone (Milstein, 1993). Anti-erythrocyte Rh antibodies were derived from hyperimmunized Rh-negative blood donors (Bye et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we examined the sequences of the VL genes expressed by the same cells from which the VH genes were derived. We found that the VL genes had Murine antibodies were obtained after secondary immulnization with the hapten phenyloxazolone (Milstein, 1993). Anti-erythrocyte Rh antibodies were derived from hyperimmunized Rh-negative blood donors (Bye et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that, in general, somatic mutations in H-and L-chain variable regions tend to occur concurrently. (29) Nevertheless, in some re- ports it is possible to find differences in the levels of mutations between the heavy and light chains. (30,31) This has been interpreted as an evidence of independent activity of the hypermutation machinery in each chain.…”
Section: Quantitative and Qualitative Analysis Of Somatic Hypermutationsmentioning
confidence: 99%
“…Initial studies suggesting the existence of an ‘I‐J‐specific’ suppressor factor secreted by T cells and TCR specificity achieved through Ig genes were refuted. Rather, the discovery of how to expand T cells in vitro, via IL‐2‐dependent T‐cell cloning , in conjunction with monoclonal antibody and flow cytometry screening technologies plus in vitro functional analyses was decisive in molecular identification for the long sought‐after TCR. The key breakthroughs came in the early 1980s with the identification in human of a clonotypic disulfide‐linked heterodimer, the Ti αβ TCR heterodimer, which together with CD3 molecules, were essential for peptide/MHC complex recognition and cellular activation .…”
Section: Introductionmentioning
confidence: 99%